Swimming With the Tide: Solidarity Wage Policy and the Gender Earnings Gap - Per-Anders Edin; Katarina Richardson (Uppsala University, Department of Economics, 1999)
The purpose of this paper is to examine the role of wage compression for the gender wage gap in Sweden during the period 1968-1991. We find that the effects of changes in the wage structure on womens wages have varied over time and have had partly counteracting effects. Changes in industry wage differentials have systematically worked against women, while the changes in the returns to human capital and unobserved characteristics have contributed to reductions in the gender wage gap. Changes in the wage structure were particularly important between 1968 and 1974 when the reduction of overall wage inequality was dramatic. In 1981, however, the wage compression effect accounted only for a minor proportion of women's relative wage gains, as compared to 1974. At this time, women gained in relative wages mainly because discrimination was mitigated and/or the gender gap in unobserved skills was reduced. Between 1981 and 1991 there is a small increase in the gender wage gap. This small increase seems to have been driven by changed inter-industry wage differentials.
urn:nbn:se:uu:diva-2457
Keywords: J16; J31; J51; 330; Gender wage differentials; trade union; wage structure; Lohndifferenzierung; Geschlecht; Fraueneinkommen